Factors Influencing Customers’ Decision to Purchase Green and Eco Friendly Products - Kumar, Dr Kapil (Innovative Research Thoughts, 2017)
This study identified different factors, determinants and other elements affecting green products purchase decision-making and provides explanations which ultimately lead to green purchase behaviour. Consumer's concern towards environment and products different functional attributes have emerged as major determinants for green purchase behaviour. This paper identifies the main predictors related to consumer's green purchase intentions and purchase behaviour. Which will facilitates policy makers and marketers in implementing and formulating strategies to encourage green product purchasing.